2021
DOI: 10.1038/s41598-021-82154-y
|View full text |Cite
|
Sign up to set email alerts
|

Modified sensory feedback enhances the sense of agency during continuous body movements in virtual reality

Abstract: The sense of agency refers to the feeling of control over one’s own actions, and through them, the external events. This study examined the effect of modified visual feedback on the sense of agency over one’s body movements using virtual reality in healthy individuals whose motor control was disturbed. Participants moved a virtual object using their right hand to trace a trajectory (Experiment 1) or a leading target (Experiment 2). Their motor control was disturbed by a delay in visual feedback (Experiment 1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 56 publications
1
38
0
Order By: Relevance
“…This sense of ‘presence’, which captures the feeling that a user is truly there in virtual world, results from the immersion the user feels as a result of realistic multisensory illusions [ 30 , 31 ]. This feeling also provides a sense of agency over the environment, increases task engagement, and can affect cognition, social behavior, and memory [ 1 , 32 , 33 ]. Naturalistic stimuli also capture and maintain attention more authentically than simple two-dimensional stimuli because they tap into more sophisticated top-down attention pathways that incorporate context, prior knowledge, and goals rather than purely feature-based attention [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…This sense of ‘presence’, which captures the feeling that a user is truly there in virtual world, results from the immersion the user feels as a result of realistic multisensory illusions [ 30 , 31 ]. This feeling also provides a sense of agency over the environment, increases task engagement, and can affect cognition, social behavior, and memory [ 1 , 32 , 33 ]. Naturalistic stimuli also capture and maintain attention more authentically than simple two-dimensional stimuli because they tap into more sophisticated top-down attention pathways that incorporate context, prior knowledge, and goals rather than purely feature-based attention [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…SoA refers to the feeling of control over one’s actions. Previous studies have demonstrated the role of SoA during continuous body movements [ 48 ]. In addition, SoA and path integration shared overlapping brain regions such as the premotor cortex and supramarginal gyrus [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, many studies have been conducted to investigate the impact of modified visual feedback on body consciousness and behavior (Slater et al, 2008;Burin et al, 2019;Keenaghan et al, 2020;Aoyagi et al, 2021), indicating that sense of agency is affected by the visual feedback. This is because the mismatch between the intended motion and the actual visual feedback directly affects the level of the sense of agency.…”
Section: Discussionmentioning
confidence: 99%